Dinámica del plancton en la primera milla náutica frente a la provincia de El Oro, Ecuador - Salcedo, Jessica (2018)
Plankton dynamics in the first nautical mile of El Oro province, Ecuador. El Oro includes different coastal and estuarine systems and the important Gulf of Guayaquil. These areas provide different ecosystem services, but with the increase of population and of the varied economic activities, the barely known local natural resources may be negatively impacted. Thus this research aimed to study plankton dynamics, productivity and ecological balance for the area during the dry season of 2012. For this, we established 17 stations and studied the monthly variation and spatial distribution of inorganic nutrients, temperature, dissolved oxygen, salinity, photic zone, plankton and fish larvae abundance and composition with standard methods, while spatial and temporal patterns where identified using cluster and multidimentional scaling analyses. Obtained results of biotic and abiotic parameters defined a pattern characteristic of productive estuarine zones as well as the existence of three specific areas associated with the natural and anthropic conditions of the area, such as: a) inner part of the Jambelí Archipelago and in front of Puná island influenced by productive activities and the hydrography of the area; B) an area, formed by the stations located in the outer estuary where the oceanic influence is evident and c) the Jambelí channel, characterized by mixing processes resulting from tides flow. This was supported by the presence of oceanic, neritic and estuarine phytoplankton; copepods with uniform distribution in the study area, and dominance of Engraulidae fish larvae, representative of this type of aquatic ecosystem. Temporally, rainfall records in May exceeded normal values, which would have influenced the high concentrations of nutrients, decrease of salinity and of the photic zone registered during this month. However, the availability of nutrients throughout the study period, allowed to maintain the composition and abundance of phytoplankton, with changes in representative species, recorded periods of greater (June to August) and lower (October to December) zooplankton abundance, could be the result of specific population patterns of present species, and the influence of the tide and the flows of the contributing river basin. A similar behavior was recorded for ichthioplankton, as a result of Anchoa macrolepidota concentrations, species, characteristics of this type of ecosystem. These patterns of spatio-temporal distribution, allowed the development of multiple abiotic and biotic interactions that determine different strategies to maintain the productivity of the area. We recommend new studies during the rainy season in Ecuador. Rev. Biol. Trop. 66(2): 836-847. Epub 2018 June 01.